PEMENUHAN HAK WARGA BINAAN LANJUT USIA DI LEMBAGA PERMASYARAKATAN PEREMPUAN (LPP) KELAS IIA BANDUNG - Gebi Joanti; Sumardhani Sumardhani (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
This study aims to examine the fulfillment of the rights of the rights of elderly prisoners in the class IIA Bandung Women’s Correctional Institutions. Elderly prisoners are a vulnerable group who often experience discrimination and lack of adequate facilities while serving their sentence. As an institution that carries out the task of guidance and protection, the Women's Correctional Institution Class IIA Bandung is expected to fulfill the rights of elderly prisoners by applicable standards and regulations. This research uses a qualitative method with a case study approach and uses purposive sampling techniques in selecting informants. The informants in the study consisted of four key informants and two supporting informants. The results showed that the fulfillment of the rights of elderly prisoners at the Class IIA Bandung Women's Correctional Institution had been fulfilled. However, in its implementation, it is still not carried out optimally because there are inhibiting factors in the form of budget limitations, and human resources in the form of professional experts. However, there are also supporting factors that encourage the achievement of the goals of the Class IIA Women's Correctional Institution such as institutional policies in implementing special programs, and the provision of facilities and infrastructure.